2005
DOI: 10.1002/chin.200517006
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Structures, and Evaluation of Laser Properties of LiYb(MoO4)2 Single Crystal.

Abstract: Crystal. -Single crystals of the title compound are prepared by the top-seeded solution growth method from Yb2(MoO4)3 using Li2MoO4 or Li2Mo2O7 as fluxes. LiYb(MoO4)2 crystallizes in the tetragonal space group I4 with Z = 2. The compound is further characterized by optical absorption and photoluminescence properties. In comparison to the Yb-stoichiometric laser crystals so far demonstrated, this new Yb stoichiometric crystal promises laser action with larger bandwidth, but higher pump threshold intensity likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 1 publication
2
8
0
Order By: Relevance
“…In fact the Yb 3+ absorption band with long high‐energy tail to red region is also seen in Fig. for LYM and also in other compounds …”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…In fact the Yb 3+ absorption band with long high‐energy tail to red region is also seen in Fig. for LYM and also in other compounds …”
Section: Resultssupporting
confidence: 60%
“…According to the far‐infrared absorption spectrum of LYM, three intense peaks have been observed at 834, 787, and 705 cm −1 , where the most intensive one is at 787 cm −1 , together with weak peaks at 895, 454, 414, and 339 cm −1 . It is suggested that the vibration peaks around 787‐880 cm −1 peak is due to MoO 4 whose phonon energy has been estimated as 800 cm −1 , and as 700‐800 cm −1 .…”
Section: Mechanism Of Yb3+ Emissionmentioning
confidence: 99%
“…Recently, an extensive crystal growth and characterization study has been conducted on single crystals of LiYb͑MoO 4 ͒ 2 (LiYbMo) grown using Li 2 MoO 4 and Li 2 Mo 2 O 7 solvents. 20 The high Yb density in this stoichiometric material ͑6.87ϫ 10 21 cm −3 ͒ results in a large peak optical absorption coefficient ͑␣ Ͼ 125 cm −1 ͒ for both polarizations. 20 Hence, very thin (of the order of 0.2 mm and less) and difficult to handle active elements will be necessary to control the reabsorption effects in the threelevel operational scheme of the Yb 3+ ion.…”
Section: Introductionmentioning
confidence: 88%
“…It corresponded to an actual crystal composition of LiGd 0.936 Yb 0.064 Mo or Yb density of 4.06×10 20 cm -3 . Xray diffraction studies lead to refinement of the Yb:LiGdMo structure in the noncentrosymmetric space group 4 I , the same as for LiYbMo [1], but different from the previously assumed centrosymmetric (scheelite) space group I4 1 /a. 4 I has two nonequivalent 2b and 2d sites occupied by Li + , Gd 3+ or Yb 3+ with specific occupancy factors.…”
Section: Crystal Growth Structure and Spectroscopymentioning
confidence: 97%
“…Recently, an extensive crystal growth and characterization study has been conducted on single crystals of LiYb(MoO 4 ) 2 (LiYbMo) [1]. The high Yb density in this stoichiometric material (6.87×10 21 cm -3 ) results in large peak optical absorption coefficient (α >125 cm -1 ) for both polarizations.…”
Section: Introductionmentioning
confidence: 98%